2017
DOI: 10.1177/0748730417697537
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Misalignment Increases C-Reactive Protein and Blood Pressure in Chronic Shift Workers

Abstract: Shift work is a risk factor for inflammation, hypertension and cardiovascular disease. This increased risk cannot be fully explained by classic risk factors. Shift workers’ behavioral and environmental cycles are typically misaligned relative to their endogenous circadian system. However, there is little information on the impact of acute circadian misalignment on cardiovascular disease risk in shift workers, independent of differences in work stress, food quality and other factors that are likely to differ be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
112
2
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(126 citation statements)
references
References 48 publications
(98 reference statements)
7
112
2
5
Order By: Relevance
“…There is experimental and epidemiologic evidence that night shift work is associated with elevated CRP levels. In human experiments, CRP levels increased among volunteers subjected to circadian misalignment through a 12 hour delay in normal sleep hours . In the present analysis, we found no association between recent night shift work and CRP levels.…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…There is experimental and epidemiologic evidence that night shift work is associated with elevated CRP levels. In human experiments, CRP levels increased among volunteers subjected to circadian misalignment through a 12 hour delay in normal sleep hours . In the present analysis, we found no association between recent night shift work and CRP levels.…”
Section: Discussioncontrasting
confidence: 76%
“…In a small trial, individuals allocated 4 hours per night in bed for 10 nights had a significant increase in C‐reactive protein (CRP) levels, a finding not observed among those allowed 8 hours per night in bed . These findings were later confirmed in another similar trial and in studies of night workers . Other studies show that sleep restriction results in glucose intolerance, elevations in blood pressure, higher levels of inflammatory cytokines, and coronary artery calcification …”
Section: Introductionmentioning
confidence: 88%
“…Interestingly, some diseases linked to unsynchronized circadian rhythms in adult human and animal models (McHill & Wright, ; Morris et al . ; Murray et al . ) have been correlated with physiological alteration induced in offspring gestated in adverse prenatal conditions (Osmond & Barker, ; Fowden et al .…”
Section: Discussionmentioning
confidence: 97%
“…Various studies have found an effect of circadian misalignment on the cardiovascular system, including increased blood pressure (Morris, Purvis, Hu, & Scheer, ; Scheer et al., ), which seems to be mainly due to increased systolic and diastolic blood pressure during the sleep period (Morris, Purvis, Hu, et al., ). Interestingly, also among chronic shift workers, 24‐hr systolic and diastolic blood pressure were increased during a laboratory protocol inducing circadian misalignment, with systolic blood pressure being mainly increased during the wake period and diastolic blood pressure being mainly increased during the sleep period (Morris, Purvis, Mistretta, Hu, & Scheer, ). While one study reported no effect of circadian misalignment on parasympathetic cardiac control (Scheer et al., ), a subsequent study by the same group found that parasympathetic cardiac control was decreased during circadian misalignment (Morris, Purvis, Hu, et al., ), which could provide a mechanistic explanation for the elevated blood pressure observed during circadian misalignment.…”
Section: Metabolic and Cardiovascular Effects Of Circadian Misalignmementioning
confidence: 99%